BEHAVIORAL ACTIVATION AND THERAPEUTIC EXPOSURE FOR POSTTRAUMATIC STRESS DISORDER: A NONINFERIORITY TRIAL OF TREATMENT DELIVERED IN PERSON VERSUS HOME‐BASED TELEHEALTH. Issue 5 (10th February 2016) - Acierno, Ron; Gros, Daniel F.; Ruggiero, Kenneth J.; Hernandez‐Tejada, B. Melba A.; Knapp, Rebecca G.; Lejuez, Carl W.; Muzzy, Wendy; Frueh, Christopher B.; Egede, Leonard E.; Tuerk, Peter W.
Abstract : Objective: Combat veterans returning to society with impairing mental health conditions such as PTSD and major depression (MD) report significant barriers to care related to aspects of traditional psychotherapy service delivery (e.g., stigma, travel time, and cost). Hence, alternate treatment delivery methods are needed. Home‐based telehealth (HBT) is one such option; however, this delivery mode has not been compared to in person, clinic‐based care for PTSD in adequately powered trials. The present study was designed to compare relative noninferiority of evidence‐based psychotherapies for PTSD and MD, specifically Behavioral Activation and Therapeutic Exposure (BA‐TE), when delivered via HBT versus in person, in clinic delivery. Method: A repeated measures (i.e., baseline, posttreatment, 3‐, 6‐month follow‐up) randomized controlled design powered for noninferiority analyses was used to compare PTSD and MD symptom improvement in response to BA‐TE delivered via HBT versus in person, in clinic conditions. Participants were 232 veterans diagnosed with full criteria or predefined subthreshold PTSD. Results: PTSD and MD symptom improvement following BA‐TE delivered by HBT was comparable to that of BA‐TE delivered in person at posttreatment and at 3‐ and 12‐month follow‐up. Conclusion: Evidence‐based psychotherapy for PTSD and depression can be safely and effectively delivered via HBT with clinical outcomes paralleling those of clinic‐based care delivered in person. HBT, thereby, addresses barriers to care related to both logistics and stigma.